PENERAPAN METODE DEMONSTRASI PADA BIDANG STUDI IPA UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS IV SDN 45 PULAU KARAM KECAMATAN KOTO XI TARUSAN - Dasni Dasni (IICET (Indonesian Institute for Counseling, Education and Therapy), 2016)
Science has important roles in our daily life. In formal education, science is taught since primary school. Based on the observation result of grade IV SDN 45 Pulau Karam Kecamatan Koto XI Tarusan, it was known that students got low scores for their science daily test which was under the minimum standard of 75%. It was an indicator of unsuccessful learning process. In order to solve this problem, teacher tried to implement the demonstration method in learning process. This method can help students in understanding the learning material. This classroom action research was aimed to improve the learning achievement of science subject of students grade IV SD Negeri 45 Pulau Karam by implementing the demonstration method in learning process. Data of research were obtained through observation sheet and test. Data were analyzed quantitatively and qualitatively. This research was held in two cycles. After cycle I, students’ learning achievement are improved which become 73%. After cycle II, students’ learning achievement improve more significantly, it becomes 91%. Based on the result of research, it can be concluded that implementation of demonstration method on science subject learning can improve the learning achievement of students grade IV SDN 45 Pulau Karam Kecamatan Koto XI Tarusan.